Implementation Of Blended Learning In Training (Inovasi: Jurnal Diklat Keagamaan, 2021)
Improving the quality of human resources is an important issue in training. Currently, the blended learning model is the most used approach that is used and is expected to improve the quality of training. The goal of this article is to analyze the learning blended model as a training strategy in training institutions.The research method using literature review from journals, focusing on the question of why blended learning is needed, how the characteristic is, how to implement it, and how effective this method is.This article analysis concludes that blended learning is needed to improve the quality and quantity of training. This training model combines face-to-face and online training approaches and practices. With a mixed learning strategy, the training become more flexible. The blended learning model can make it easier for participants to access theory and training materials, increase the learning motivation and independence of participants that leads the class to be more effective. This blended learning model can be applied as a training model in educational institutions. To improve the quality of blended learning during session, it is necessary to have adequate informatics infrastructure technology facilities and the independence of the participants.
Keywords: E-learning, Blended learning, training